2009
DOI: 10.1111/j.1471-4159.2008.05787.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species regulate F‐actin dynamics in neuronal growth cones and neurite outgrowth

Abstract: Reactive oxygen species are well known for their damaging effects due to oxidation of lipids, proteins and DNA that ultimately result in cell death. Accumulating evidence indicates that reactive oxygen species also have important signaling functions in cell proliferation, differentiation, cell motility and apoptosis. Here, we tested the hypothesis whether reactive oxygen species play a physiological role in regulating F‐actin structure and dynamics in neuronal growth cones. Lowering cytoplasmic levels of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
92
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 61 publications
(150 reference statements)
16
92
0
1
Order By: Relevance
“…2A, arrows). These results are consistent with the finding that actin at the growth cone of Aplysia bag cells is disorganized after NOX inhibition (Munnamalai and Suter, 2009). Second, based on the possible influence of NOX on the integrity of the actin cytoskeleton, we evaluated filopodial dynamics at the tip of the axon as a parameter for actin polymerization.…”
Section: Contribution Of the Nox Complex To Actin Cytoskeleton Dynamicssupporting
confidence: 82%
See 2 more Smart Citations
“…2A, arrows). These results are consistent with the finding that actin at the growth cone of Aplysia bag cells is disorganized after NOX inhibition (Munnamalai and Suter, 2009). Second, based on the possible influence of NOX on the integrity of the actin cytoskeleton, we evaluated filopodial dynamics at the tip of the axon as a parameter for actin polymerization.…”
Section: Contribution Of the Nox Complex To Actin Cytoskeleton Dynamicssupporting
confidence: 82%
“…Oxidation of actin decreases its ability to polymerize (Hung et al, 2011(Hung et al, , 2010Sakai et al, 2012;Terman and Kashina, 2013). However, inhibition of NOX reduces both the F-actin content at the growth cone and the retrograde actin flow in neurons, suggesting a crosslink between NOX and actin dynamics (Munnamalai and Suter, 2009;Munnamalai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of PC12 cells with either nicotinamide adenine dinucleotide phosphate (NADPH) oxidase inhibitor, diphenylene iodonium, catalase, or N-acetylcysteine negated the nerve growth factor response and blocked neuronal differentiation (45,48). Furthermore, NADPH oxidase has been implicated in hippocampal long term potentiation, neuronal growth cone formation, and neurite outgrowth (49,50). However, Tsatmali et al (51) showed that ROS production does not influence the probability of a cell becoming a neuron during development.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between ROS and actin cytoskeleton has long been recognized (Wilson and González-Billault, 2015). In mammalian cells, ROS regulate actin rearrangements associated with cellular processes such as cell adhesion, migration, wound repair, as well as neurite outgrowth (Chiarugi et al, 2003;Fiaschi et al, 2006;Munnamalai and Suter, 2009;Sakai et al, 2012;Taulet et al, 2012;Xu and Chisholm, 2014). In plant cells, ROS signaling is required for actin remodeling during the self-incompatibility response in pollen tubes and abscisic acid-induced stomatal closure (Wilkins et al, 2011;Li et al, 2014c).…”
mentioning
confidence: 99%